Prevalence of Antimicrobial Resistance and Characteristics of Escherichia coli Isolates From Fecal and Manure Pit Samples on Dairy Farms in the Province of Québec, Canada - Massé, Jonathan; Lardé, Hélène; Fairbrother, John M.; Roy, Jean-Philippe; Francoz, David; Dufour, Simon; Archambault, Marie (Frontiers in Veterinary Science, 2021)
Antimicrobial resistance (AMR) is an important burden for public health and veterinary medicine. For Québec (Canada) dairy farms, the prevalence of AMR is mostly described using passive surveillance, which may be misleading. In addition, the presence of extended spectrum β-lactamase (ESBL)/AmpC producing Escherichia coli is unknown. This observational cross-sectional study used random dairy farms (n = 101) to investigate AMR and extended spectrum β-lactamase (ESBL)/AmpC producing Escherichia coli. Twenty antimicrobials were tested on E. coli isolates (n = 593) recovered from fecal samples (n = 599) from calves, cows, and the manure pit. Isolates were mostly susceptible (3% AMR or less) to the highest priority critically important antimicrobials in humans. The highest levels of AMR were to tetracycline (26%), sulfisozaxole (23%) and streptomycin (19%). The resistance genes responsible for these resistances were, respectively: tet(A), tet(B), sul1, sul2, sul3, aph(3”)-Ib (strA), aph(6)-Id (strB), aadA1, aadA2, and aadA5. ESBL analysis revealed two predominant phenotypes: AmpC (51%) and ESBL (46%) where blaCMY−2 and blaCTX−M(blaCTX−M−1, blaCTX−M−15, and blaCTX−M−55) were the genes responsible for these phenotypes, respectively. During this study, 85% of farms had at least one ESBL/AmpC producing E. coli. Isolates from calves were more frequently resistant than those from cows or manure pits. Although prevalence of AMR was low for critically important antimicrobials, there was a high prevalence of ESBL/AmpC-producing E. coli on Quebec dairy farms, particularly in calves. Those data will help determine a baseline for AMR to evaluate impact of initiatives aimed at reducing AMR.